What Drives Utilization of Primary Care Facilities in Vietnam? : Evidence from a Facility Survey - Vu, Lan TH (World Bank, Washington, DC, 2019)
This analysis aims to assess the association between commune health station (CHS) service readiness and health service utilization to inform the design of a World Bank project and policies to strengthen primary health care in Vietnam. Using data drawn from the 2015 Vietnam district and commune health facility survey (DCHFS), a series of multivariate negative binomial regressions was estimated to measure the association between domains of service readiness and CHS utilization rates (average number of visits per capita). To conclude, investments in improving facility infrastructure (especially ensuring that facilities have the mandated number of rooms and building area), making available essential equipment items, and enabling the CHS to provide hypertension and diabetes services, whether made independently or together, would all likely increase CHS utilization. Investment in CHSs in zone 3 and zone 2 should be prioritized over investments in zone 1, since investments in the former would result in the highest utilization rates.